Farmers’ perceptions of navy bean (Phaseolus vulgaris L.) production constraints, preferred traits and farming systems and their implications on bean breeding: a case study from South East Lowveld region of Zimbabwe - Mutari, Bruce; Sibiya, Julia; Nchanji, Eileen Bogweh; Simango, Kennedy; Gasura, Edmore (Springer, 2021)
Background Navy bean is an important legume crop in Zimbabwe. Although its production in Zimbabwe is limited by multiple constraints including biotic, abiotic and socio-economic, there is no documented evidence. Thus, this study aimed at identifying farmers’ production constraints, preferred traits and cultivars of navy bean, and strategies used to mitigate some of these constraints.